Overview of High Speed Gear Transmission Technology and Equipment - Wu Luji Geng Fuzhen (Jixie chuandong, 2019)
High-speed gear transmission technology and equipment are widely used. The application characteristics, development status and development trend of high-speed gear transmission under different conditions is briefly described, the problems and challenges in the development of high-speed gear transmission in energy and chemical industries of China are analyzed, and the countermeasures for high-speed gear transmission technology of China are proposed. The reference for the research and development of equipment is provided.